Motifs in Language and Text 2017
DOI: 10.1515/9783110476637-008
|View full text |Cite
|
Sign up to set email alerts
|

Dependency Distance Motifs in 21 Indo- European Languages

Abstract: This paper applies the notion of linguistic motif to investigating the linear arrangement of dependency distance (DD) in Indo-European and its implicational meanings in language typology. A series of DD-motifs operating in a decreasing, increasing or equal magnitude are introduced. We first describe the frequency distribution of DD-motifs, and observe a preference for decreasing DD-motifs in human languages. Moreover, we further investigate the role of DDmotifs in controlling the syntactic complexity. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…So far, the empirical description of the statistics of motif sequences has been used for the comparison of authors (Biemann et al, 2016; Al Rozz and Menezes, 2018), texts (Chen, 2017), genres (Wang, 2017), languages (Chen and Liang, 2017; Jing and Liu, 2017; Mikros and Macutek, 2017), and for classification purposes (Köhler and Naumann, 2010; Liu and Liang, 2017). Given the correlation between word order and human cognitive functions (Dryer, 1992), the investigations into the language sequential units relative of function words distribution can provide a better illustration of the syntactic processing mechanisms attributing different interpreting styles and complement with the previous results based on grammatical annotations.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the empirical description of the statistics of motif sequences has been used for the comparison of authors (Biemann et al, 2016; Al Rozz and Menezes, 2018), texts (Chen, 2017), genres (Wang, 2017), languages (Chen and Liang, 2017; Jing and Liu, 2017; Mikros and Macutek, 2017), and for classification purposes (Köhler and Naumann, 2010; Liu and Liang, 2017). Given the correlation between word order and human cognitive functions (Dryer, 1992), the investigations into the language sequential units relative of function words distribution can provide a better illustration of the syntactic processing mechanisms attributing different interpreting styles and complement with the previous results based on grammatical annotations.…”
Section: Introductionmentioning
confidence: 99%
“…As the three correlation-related analyses all show a significant influence of article type on MDD and DDI, it could be claimed that on the whole there is an effect of native language transfer on the MDD and DDI of English L2 academic writing. Currently, no study has been found to examine the MDD and DDI of all languages in the world due to various reasons, though some studies have investigated the DDs of some languages, such as Chen and Gerdes (2020) , Jing and Liu (2017) , Futrell et al (2015) and Liu (2008) . However, examining studies such as Liu (2008) reveals a trend: the greater the MDD in the background language of English L2 academic writings, the longer the MDD tends to be in English L2 academic writings themselves.…”
Section: Resultsmentioning
confidence: 99%
“…As the dependency treebanks are getting dominant, studies based on dependency grammar start to take lead. We can find recent studies discussing the relations between sentence lengths, tree heights, tree widths, and mean dependency distances (Jing & Liu, 2017;.…”
Section: The Relation Between Dependency Distance and Frequency 1 Intmentioning
confidence: 99%